Clinical spectrum associated with positive ANCA titres in 94 consecutive patients: is there a relation with PR-3 negative c-ANCA and hypergammaglobulinaemia ?. Issue 3 (1st March 1998) - Blockmans, D; Stevens, E; Mariën, G; Bobbaers, H
Abstract : OBJECTIVE: To calculate the positive predictive value (ppv) of cytoplasmic anti-neutrophil cytoplasmic antibodies (c-ANCAs) and anti-proteinase 3 (PR 3) antibodies for Wegener's granulomatosis (WG) and to evaluate their association with other diseases. METHODS: The clinical files of all 94 patients who had a positive c- or perinuclear (p)-ANCA test, or both, in the laboratory of the University Hospital, Leuven between April 1995 and March 1996 and who attended the Internal Medicine Department of the hospital were retrospectively studied. RESULTS: Of the 94 patients with ANCAs (fluorescence titre ⩾ 1/40), 57 were c-ANCA positive and 45 p-ANCA positive (eight were simultaneously c- and p-ANCA positive). Of the 57 c-ANCA positive patients, 23 had WG. The ppv for WG thus was 40%. This value did not increase by defining a higher threshold for a positive ANCA. There was not a good relation between ANCA titres and disease activity in the WG patients, nor was there a relation between anti-PR 3 antibody levels and WG disease activity. The ppv of anti-PR 3 antibodies for WG however was very high (85%). There was a positive correlation between the level of (hyper) gammaglobulinaemia and c-ANCA titres in those patients with final diagnoses not known to be associated with c-ANCA. Forty five patients had positive p-ANCAs. The largest group were those with inflammatory bowel disease (n = 20, of whom the majority had colitis ulcerosa or primary sclerosing cholangitis, or both); the great majority of these patients had no anti-myeloperoxidase antibodies. Vasculitis was present in eight patients, of whom two had WG (both were also c-ANCA positive). CONCLUSION: There is a low ppv of c-ANCAs for WG, caused by a high percentage of PR 3 negative, positive c-ANCA determinations, possibly related to hypergammaglobulinaemia. Anti-PR 3 antibodies have a high ppv for WG. However, neither c-ANCA titre, nor the level of anti-PR 3 antibodies correlated with the activity of the disease.